2020
DOI: 10.3389/fmicb.2020.550674
|View full text |Cite
|
Sign up to set email alerts
|

Positive Selection of ORF1ab, ORF3a, and ORF8 Genes Drives the Early Evolutionary Trends of SARS-CoV-2 During the 2020 COVID-19 Pandemic

Abstract: In this study, we analyzed full-length SARS-CoV-2 genomes from multiple countries to determine early trends in the evolutionary dynamics of the novel COVID-19 pandemic. Results indicated SARS-CoV-2 evolved early into at least three phylogenetic groups, characterized by positive selection at specific residues of the accessory proteins ORF3a and ORF8. Also, we are reporting potential relevant sites under positive selection at specific sites of non-structural proteins nsp6 and helicase. Our analysis of co-evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 60 publications
3
92
2
3
Order By: Relevance
“…example, artefactual biases in mutational processes could confound signatures of mutational hotspots [29][30][31][32][33][34]. The issue of whether or not recombination has occurred during the outbreak is critical to the immunological battles against the virus and is under intense debate [7,[35][36][37][38][39][40][41]. Because many tests of recombination assume that all mutations can only occur once at each site, recurrent mutation and systematic errors can confound signatures of recombination [7,27,36].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…example, artefactual biases in mutational processes could confound signatures of mutational hotspots [29][30][31][32][33][34]. The issue of whether or not recombination has occurred during the outbreak is critical to the immunological battles against the virus and is under intense debate [7,[35][36][37][38][39][40][41]. Because many tests of recombination assume that all mutations can only occur once at each site, recurrent mutation and systematic errors can confound signatures of recombination [7,27,36].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Of note, for the first time, Velazquez-Salinas et al identified the potential relevance of amino acid Y5865C in ORF1ab, showing that this residue is experimenting directional selection. Also, the increased evolutionary rate of ORF10 was identified by Velazquez-Salinas et al ( Velazquez-Salinas et al, 2020 ). Moreover, the exoribonuclease (ExoN) of NSP14 knockout mutant assays showed the replication roles of enzymatic activity in MERS-CoV and SARS-CoV-2 ( Ogando et al, 2020 ).…”
Section: Introductionmentioning
confidence: 78%
“…Using the genomic diversity of mutations in early SARS-CoV-2 strains, scientists have identified two distinct mutations, i.e., S or L type, with the S type considered more aggressive and faster spreading (Tang et al, 2020). From the analysis of early trends in the COVID-19 evolutionary patterns, Velazquez-Salinas et al for the first time identified the effect of mutation ORF1ab:5865 as a factor of phylogenetic divergence of SARS-CoV-2 ( Velazquez-Salinas et al, 2020 ). Our analysis of genetic variation in early SARS-CoV-2 strains found that most variations were in ORF1ab, and most variations in ORF1ab were nonsynonymous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 198 sites on the viral genome containing recurrent mutations and 80 viral lineages were identified by May 5,6 . Sites on the SARS-CoV-2 genome are still undergoing positive selection 7,8 . Variants of the D614G and N501Y strains (both located on the S gene) have generated global concern for increased transmissibility with little evidence of association with disease severity [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%